PELATIHAN MANAJEMEN PEMBELAJARAN DIGITAL DAN PLATFORM EDUKASI BAGI PESERTA DIDIK SMA SMK DI BANGKA TENGAH - Febiansyah, Hidayat; Lili Indah Sari; Probonegoro, Wishnu Aribowo; Isnanto, Burham; Nur, Muchamim (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
The issue of limited digital competence in learning at SMA Negeri Namang, Bangka Tengah, requires serious attention due to its impact on the quality of education and students' preparedness for the digital era. This community service project aimed to improve digital learning management competence and mastery of educational platforms through a comprehensive training approach for 11th-grade students from the science and social studies departments. The activity was conducted using an interactive learning and hands-on practice approach over 2 days, involving 35 students through theory, practice, and continuous evaluation sessions. The material covered included the fundamentals of digital learning, managing online educational platforms, and techniques for optimizing learning media, with a total duration of 16 learning hours. The results showed an average competence increase of 68.5%, with a participant satisfaction level of 89.7% and an improvement in educational platform management skills of 72.3%. Program evaluation indicated a significant transfer of knowledge, with direct implementation in digital learning projects. This community service activity successfully and measurably improved students' digital competence and provided tangible benefits in the form of practical skills in digital learning management